LA SIMETRÍA EN EL ARTE: LA LÓGICA DEL ESQUEMA - García García, Ignacio (Imafronte, 1997)
In the evolution of mankind , the symmetrical structure arises as a necessity to put order into chaos. The vertical line progressively assirmes the role of referential axis around which ist is possible to order the difrerent elements, with the aim to define coherent groups. Behind its facile appearance, the symmetrical structure has ofrered art, and more specifically religious art, the possibility to express the concepts of importante and hierarchy, using the topographical values of the picture. Symmetry, closely connected to the concept of harmony, is likewise structured around unity and variety, both in suficient proportion to suggest the sensation of coherente without losing an inferest in re-discovery. Moreover when a didactic function is the prime objective. Religious Art has over the centuries sought. throught he use of the symmetrical scheme, the visual manifestation of fhe supernatural dimension, beyond the frontier of the merely everyday, product in occasions of coincidence and sometimes of chance. Concepts thar are clearly remove, from the essence.